2009
DOI: 10.1073/pnas.0906560106
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic signaling accelerates and synchronizes cardiac ryanodine receptor response to a single L-type Ca 2+ channel

Abstract: As the most prototypical G protein-coupled receptor, ␤-adrenergic receptor (␤AR) regulates the pace and strength of heart beating by enhancing and synchronizing L-type channel (LCC) Ca 2؉ influx, which in turn elicits greater sarcoplasmic reticulum (SR) Ca 2؉ release flux via ryanodine receptors (RyRs). However, whether and how ␤AR-protein kinase A (PKA) signaling directly modulates RyR function remains elusive and highly controversial. By using unique single-channel Ca 2؉ imaging technology, we measured the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 39 publications
(85 reference statements)
6
54
0
1
Order By: Relevance
“…As a result of cBIN1 redistribution, phosphorylated RyRs is recruited to cBIN1-microdomains to couple with LTCCs at the t-tubule membrane. Thus, cBIN1 controls β-AR-dependent LTCC-RyR coupling at dyads during acute stress (Fu et al, 2016), improving CICR gain and calcium transient as observed previously (Zhou et al, 2009). When BIN1 is reduced, RyR recruitment into dyads will be impaired, accumulation of uncoupled receptors outside of dyads not only limits efficient CICR but also forms leaky receptor clusters, impairing cardiac contractility and increasing arrhythmia risks (Hong et al, 2014).…”
Section: The Role Of Bin1 In T-tubule Microdomain Organization and Fumentioning
confidence: 65%
“…As a result of cBIN1 redistribution, phosphorylated RyRs is recruited to cBIN1-microdomains to couple with LTCCs at the t-tubule membrane. Thus, cBIN1 controls β-AR-dependent LTCC-RyR coupling at dyads during acute stress (Fu et al, 2016), improving CICR gain and calcium transient as observed previously (Zhou et al, 2009). When BIN1 is reduced, RyR recruitment into dyads will be impaired, accumulation of uncoupled receptors outside of dyads not only limits efficient CICR but also forms leaky receptor clusters, impairing cardiac contractility and increasing arrhythmia risks (Hong et al, 2014).…”
Section: The Role Of Bin1 In T-tubule Microdomain Organization and Fumentioning
confidence: 65%
“…The use of H9c2 cells, which express β-adrenergic receptors ( A key mediator of the differences between undifferentiated and differentiated H9c2 cardiomyoblasts regarding ISO toxicity difference may be calcium-mediated downstream activation of signaling pathways, which follows through cAMP/PKA activation (Zhou et al, 2009, Mann et al, 1992. Increased basal calcium has been previously described in several models of cell differentiation, including cardiac cells (Fu et al, 2006), mouse embryonic stem cells (ES) (Metzger et al, 1994), human induced pluripotent stem cells (hiPSCs) (Lee et al, 2011) and rat neonatal cardiomyocytes (Gomez et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of RyR2 at Ser2808 enhances the Po of the channel by enhancing its sensitivity to cytosolic [Ca 2+ ] in planar lipid bilayers (9,10). While it is well established that increasing I Ca,L and SR Ca 2+ load enhance SR Ca 2+ release (11), it is controversial as to whether increasing RyR2 Po has similar effects (3,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In this study, we have used mice engineered with RyR2 that cannot be PKA phosphorylated (21) to directly address the role of PKA phosphorylation of RyR2 in regulating cardiac contractility.…”
Section: Introductionmentioning
confidence: 95%